Strategies for improved shock wave lithotripsy. - McAteer, J; Bailey, MR; Williams, J; Cleveland, R; Evan, A (2005)
Research in lithotripsy that started with the effort to characterize acute shock wave damage to the kidney has led to advances on several fronts, including discovery of strategies that have improved clinical treatment. It is appreciated now that shock wave trauma is primarily a vascular lesion, that injury is dose dependent, and that hemorrhage can be severe and can lead to a permanent loss of functional renal mass. Studies of the renal functional response to lithotripsy have shown that shock wave treatment triggers vasoconstriction in the kidney. This finding has been turned to advantage, and it is now known that when treatment is begun using low amplitude pulses, subsequent high amplitude shock waves are far less damaging. Thus, when shock waves are delivered judiciously, treatment can have a protective effect. The finding that cavitation is a key mechanism in vessel rupture has led to the development of novel experimental methods of shock wave delivery that can suppress bubble expansion and minimize tissue damage. Progress has also been made in understanding the physical mechanisms involved in stone comminution, and it is seen that the forces generated by cavitation, shear stress and circumferential squeezing act synergistically to fragment stones. Recent work suggests that a broad focal zone may be an advantage, allowing stones to be broken with lower amplitude pulses. Cavitation has been shown to play a critical role in reducing stone fragments to a size that can be voided. Cavitation is also the factor that limits the rate at which treatment can be performed, as stones break significantly better at slow rate than at fast ratean observation from basic research that is now appreciated in clinical practice. The current environment in lithotripsy research is encouraging. There is great interest in developing new technology, and in finding ways to improve how lithotripsy is performed.